A comparison study between gross tumor volumes defined by preoperative magnetic resonance imaging, postoperative specimens, and tumor bed for radiotherapy after breast-conserving surgery. Issue 2 (January 2017) - Zhang, Aiping; Li, Jianbin; Wang, Wei; Wang, Yongsheng; Mu, Dianbin; Chen, Zhaoqiu; Shao, Qian; Li, Fengxiang
Abstract: Background: The identification and contouring of target volume is important for breast-conserving therapy. The aim of the study was to compare preoperative magnetic resonance imaging (MRI), postoperative pathology, excised specimens' (ES) size, and tumor bed (TB) delineation as methods for determining the gross tumor volume (GTV) for radiotherapy after breast-conserving surgery (BCS). Methods: Thirty-three patients with breast cancer who underwent preoperative MRI and radiotherapy after BCS were enrolled. The GTVs determined by MRI, pathology, and the ES were defined as GTVMRI, GTVPAT, and GTVES, respectively. GTVMRI+1 was defined as a 1.0-cm margin around the GTVMRI . The radiation oncologist delineated GTV of the TB (GTVTB ) using planning computed tomography according to ≥5 surgical clips placed in the lumpectomy cavity (LC). Results: The median GTVMRI, GTVMRI+1, GTVPAT, GTVES, and GTVTB were 0.97 cm 3 (range, 0.01–6.88), 12.58 cm 3 (range, 3.90–34.13), 0.97 cm 3 (range, 0.01–6.36), 15.46 cm 3 (range, 1.15–70.69), and 19.24 cm 3 (range, 4.72–54.33), respectively. There were no significant differences between GTVMRI and GTVPAT, GTVMRI+1 and GTVES, GTVES and GTVTB ( P = 0.188, 0.070, and 0.264, respectively). GTVMRI is positively related with GTVPAT . However, neither GTVES nor GTVTB correlated with GTVMRI ( P = 0.071 and 0.378, respectively). Furthermore, neither GTVES nor GTVTB correlated with GTVMRI+1 ( P = 0.068 and 0.375, respectively). Conclusion: When ≥5 surgical clips were placed in the LC for BCS, the volume of TB was consistent with the volume of ES. Neither the volume of TB nor the volume of ES correlated significantly with the volume of tumor defined by preoperative MRI.